Impact analysis of the implementation of the PIBID Natural Sciences (UFF) Subproject on the partner school, supported by CHIC software (Research, Society and Development, 2020)
This article aimed to analyze the impacts of the implementation of the PIBID Natural Science (UFF) Subproject, at the Escola Municipal “Escola Viva” Professora Edy Belloti, located in Santo Antônio de Padua / RJ, between 2014 and 2015. For the production and collection of data, a questionnaire was applied to 57 students of basic education, which were analyzed according to the similarity analysis method supported by the software CHIC (Cohesive hierarchical implicative classification). Based on the results obtained, it is possible to affirm that the actions developed by the subproject team reflected in the increase of students' performance, interest and participation in science classes and in internal and external evaluations. The results corroborated the statement that PIBID is an important public policy of teacher training to improve the quality of public basic education.